Considerations for Monitoring School Health and Nutrition Programs - Schultz, Linda; Ruel-Bergeron, Julie (Frontiers in Public Health, 2021)
School health and nutrition (SHN) interventions are among the most ubiquitous public health investments and comprise a key mechanism for reaching populations that are otherwise difficult to reach through the health system. Despite the critical role of monitoring these multisectoral programs to enable data-informed adaptive programming, information to guide program implementers is scant. This manuscript provides an overview of how monitoring indicators can be selected across a SHN program’s logical framework, with specific examples across five SHN implementation models. Adaptation of SHN programs in times of school closures, such as those currently being experienced globally due to the emergence of COVID-19, is also addressed. Key aspects of SHN program monitoring are explored, including: (1) why monitor; (2) what to measure; (3) how to measure; and (4) who measures. In situations of school closures, strategies to shift both program activities and corresponding monitoring mechanisms are critical to understanding the rapidly evolving situation and subsequently guiding policy actions to protect vulnerable populations.